2011
DOI: 10.1089/thy.2010.0332
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors and Treatment Outcomes of 100 Cases of Anaplastic Thyroid Carcinoma

Abstract: Although the prognosis of most patients with ATC continues to be poor, surgery, radiotherapy, and a combination of both improved the survival of patients with ATC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

12
108
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(127 citation statements)
references
References 46 publications
12
108
2
3
Order By: Relevance
“…The median OS reported in the current study was 3 months which is less than the 3.9 months median OS of 100 patients reported by Akaishi et al 12 , but similar to the 2.8 median OS of 13 patients studied by Lim et al 26 . Several studies have examined the factors affecting prognosis in patients with ATC.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The median OS reported in the current study was 3 months which is less than the 3.9 months median OS of 100 patients reported by Akaishi et al 12 , but similar to the 2.8 median OS of 13 patients studied by Lim et al 26 . Several studies have examined the factors affecting prognosis in patients with ATC.…”
Section: Discussionsupporting
confidence: 72%
“…Several studies have examined the factors affecting prognosis in patients with ATC. The prognostic factors include patient age, tumor size, and clinical stage which should be considered when evaluating patients for treatment 12 . Univariate and multivariate analyses of factors affecting survival by Kihara et al showed that complete surgery was an independent prognostic factor 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multimodal therapies, including surgery, radiation and chemotherapy, are generally used to manage this highly malignant disease. However, the prognosis is poor and the majority of the patients succumb to the disease within a year, with a median survival time of <6 months from the initial diagnosis (1)(2)(3). Recently, new approaches to treating ATC by targeted molecular markers have been developed to overcome therapeutic resistance (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%
“…Multimodality treatment (combination of surgery, radiation and chemotherapy) is the most effective therapy that has been shown to improve outcome for stages IVA, and resectable stage IVB disease with a 1 year survival up to 70%, 2 year survival of 60%, and 50% living beyond 2.5 years with a median survival of 5 years [3,4]. Current treatment guidelines recommend surgical resection if possible for locoregional disease (stage IVA and resectable IVB) and stabilization of airway patency in all patients.…”
mentioning
confidence: 99%